A prosódia na leitura da criança disléxica - Luciana Mendonca Alves (2007)
The present work aims to get to know the prosodic functioning of the reading aloud of the dyslexic children. We initially present a bibliographical revision that consists of the main theories on the normal development of the written language and its linguistic, neurological and cognitive aspects. We go through a conceptualization of the term dyslexia, its description and etiology. After that, we introduce the field of study of theprosody and its application to the studies of dyslexia. Our methodology consisted of the recording of the reading of a text, with posterior activity of recalling and interpretation of this text by 40 students, being 10 dyslexic (the clinical group) and 30 of the non-clinical group, all aged between 9 and 14 years, attending the third to fifth grades. The data was analyzed acoustically, using the WinPitch program, apart from a perceptual analysis. The temporal and melodic prosodical aspects of the oralreading and of the students recount were analyzed and correlations between these findings and the data of the objective tests of interpretation were carried out. The results allowed us to delineate a trend in the entonative and temporal structure of the reading aloud of the children of the two groups studied, pointing to peculiar features, such as aspects related to the variation of the basic frequency (demonstrating clearly a restriction in the ability to vary the melody and also to mark the frasal modality through this resource), aspects related to the temporal processing (extreme use of the pauses and out of its usual localization, reading speed and reduced articulation) and the difficulties in marking out rhythm and prominent tonic, clearly associated with a profile that can be attributed to the dyslexic children studied. The prosody is presented, in this context, as a consequence of the abilities of interpretation and ofdecoding, also serving as a diagnostic measure of these capacities.